Ramesside Hieratic Stela of the Sandal Maker Penone in the Egyptian Museum Cairo (TR. 27.6.24.3) - Hassan, Khaled.
The hieratic stela (TR. 27.6.24.3) in the Egyptian Museum Cairo represents an interesting deposition which belongs to the sandal maker, Penone, and a woman named Ta‘at. This stela represents one of the earliest known incised hieratic examples from the Ramesside Period. The article presents a full transcription and translation with commentary on the text. Particular attention is paid to the palaeography of the text. It also shows the purpose of writing this kind of subject on this stela instead of an ostracon or papyrus. The choice of the hieratic rather than the hieroglyphic script for this stela is examined as well.